Pengaruh Karakteristik Individu Terhadap Partisipasi Kerja Pemuda Di Provinsi Banten Tahun 2020 - Sukma Direja; Pradhita Andiah Permani (Jurnal Ekonomi Pembangunan, 2021)
From the overall human resources, youth is the group with the most potential, both in terms of quantity and quality. This study used the logit model to determine the effect of individual characteristics on youth labor participation in Banten province. By using data from BPS, from this research, it can be seen that youth labor participation in Banten province is influenced by age, age squared, gender, marital status, length of schooling, job training that has been attended, youth status as head of household, number of household members, the head of the household gender, the length of school for the head of the household, and household income.